Changes in Gut Microbiota Composition after Bariatric Surgery: a New Balance to Decode - Palmisano, Silvia; Campisciano, Giuseppina; Silvestri, Marta; Guerra, Martina; Giuricin, Michela; Casagranda, Biagio; Comar, Manola; de Manzini, Nicolò (Journal of gastrointestinal surgery, 2020)
Background Recently, the link between obesity and gut microbiota has become a focus for research. This study shed some light on the modification of postoperative gut microbial composition after bariatric surgery. Methods A prospective longitudinal study on healthy lean subjects and patients who underwent bariatric surgery (Roux-en-Y gastric bypass and laparoscopic sleeve gastrectomy) was carried out. Anthropometric and metabolic data, smoking, food preferences data, and stool samples were collected from lean subjects and from obese patients before and 3 and 6 months after surgery (T0, T3, and T6, respectively). Results We collected stool samples from 25 obese patients before surgery and 3 and 6 months thereafter and from 25 normal weight patients. After Roux-en-Y gastric bypass, Yokenella regensburgei ( p < 0.05), Fusobacterium varium ( p < 0.05), Veillonella dispar / atypica ( p < 0.05), and Streptococcus australis / gordonii ( p < 0.05) were transiently identified in the gut at T3. Roux-en-Y gastric bypass patients had a permanent increase in Akkermansia muciniphila ( p < 0.05), which is associated with healthy metabolism, both at T3 and T6. There were no significant changes in gut microbiota in laparoscopic sleeve gastrectomy patients. Conclusions In our study, Roux-en-Y gastric bypass induced major microbial differences and greater weight loss compared with laparoscopic sleeve gastrectomy. Analyzing the microbiota composition, a proliferation of potential pathogens and the onset of beneficial bacteria was observed. The effects of these bacteria on human health are still far from clear. Understanding the mechanisms of action of these bacteria could be the keystone in developing new therapeutic strategies for obesity.